Coupling relationships between vegetation and soil in different vegetation types in the Ulan Buh Desert and the Kubuqi Desert - Han, Gaoling; Huo, Jianqiang; Hu, Rui; Gong, Xiangwen; Nan, Yicong; Lian, Yuchao; Zhang, Zhishan (Frontiers in Plant Science, 2025)
IntroductionDesertification is a globally recognized ecological issue that poses severe threats to the environment, economic and social systems. Revegetation is the primary means to combat desertification, yet the effectiveness of revegetation practices requires reasonable quantification.MethodsTo identify appropriate planting patterns for revegetation in different deserts and provide a basis for vegetation reconstruction in deserts, we conducted a comprehensive survey in the Ulan Buh Desert and the Kubuqi Desert of the Northern China. Data on vegetation and soil were collected from 54 representative sites, covering both natural and revegetation communities.ResultsThe findings revealed that the diversity of herbaceous and woody species, and soil nutrient content increased after revegetation, in comparison to adjacent moving sand dunes. Additionally, the species diversity and soil conditions in revegetation areas, gradually approached those of natural vegetation communities, indicating a succession towards a state resembling natural conditions. Variations in the coupling of vegetation-soil systems were observed among different community types in both deserts. Notably, the communities dominated by Caragana korshinskii and Artemisia ordosica exhibited the strongest coupling in the vegetation-soil system, driven primarily by soil water and nutrients, as well as vegetation growth.DiscussionEvaluation of vegetation-soil system coupling effect was used to evaluate the effectiveness of vegetation restoration and species selection in the wo deserts, which can serve as a reference for vegetation reconstruction and ecological restoration in desert areas.